Production of α-amylase by immobilized bacillus subtilis in polymeric polyHIPE matrix - Jimat, Dzun Noraini; Harwood, Colin; Akay, Galip (Springer Science+Business Media, 2013)
The microcellular polymer known as polyHIPE polymer (PHP), with modified physico-chemical characteristics, was developed as a cell matrix for the immobilization of the starch-degrading bacterium, Bacillus subtilis. Suspension of B. subtilis spores was inoculated into a synthesized PHP matrix which is chemically modified, and this PHP matrix was named sulphonated PHPs (SPHPs). These inoculated spores were then activated by supplying continuously well-aerated culture medium (LB medium) and placed in a 37 °C constant temperature room for 24-h incubation. The growth and enzyme productivity data were evaluated and compared. Three different pore and interconnect sizes of SPHPs were evaluated: 42.0 ± 0.61, 36.0 ± 0.50 and 30.0 ± 0.64 μm. The collected samples obtained from the 24-h cultivation were used to determine α-amylase productivity and the loss of cells from the matrices. The morphology, viability and proliferation of the immobilized cells on PHP matrices were observed by scanning electron microscopy (SEM). The SPHP with a pore size of 36.0 μm performed better with respect to the production of α-amylase and the penetration of cells through the whole matrix compared to other SPHPs. The data showed that the total productivity of α-amylase enzyme produced by immobilized cells (on the basis of SPHP volume) was 7.6-fold higher than the batch cell culture. However, if productivity was determined on the basis of used total volume of nutrient medium, that of the immobilized cells was relatively low compared to batch cell culture.